Nanostructuring of metal surfaces by laser ablation - Toro Salazar, Cinthya Emma (2016)
Irradiation of materials such as iron and silicon with single nanosecond laser pulses produces nanostructures on its surfaces. Nevertheless, the deposition before irradiation of thin films on the silicon?s surfaces can modify the shapes of these structures. Upon laser irradiation, different effects are produced on the surfaces of monocrystalline silicon waferscoated with a thin film of Si3N4 than on that of bare bones. After irradiation with an Nd:YAG laser pulse of 532 nm, the coated silicon surface presents a nanostructure that, due to its hydrophobic behavior, can be used for biological applications such cell growth. On the other hand, the nanostructures formed on the surface of metals, such as iron, make them more resistant to oxidation processes by changing their oxidation potentials.